FEATURES OF THE MATHEMATICAL MODELING OF FOUNDATIONS INTERACTION WITH COMPACTING SOILS, WITH ANISOTROPIC PROPERTIES - Vynnykov, Yu. L.; Aniskin, O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Features of the mathematical modeling of foundations interaction with compaction soils with anisotropic properties, by ultimate elements method in the physically and geometrically non-linear presentation are confirmed. To prove this fact it was obtained henomenological soil model that describes its state during building, work of compacted subsoil. Famous physical correlations of orthotropic medium were used in model. Modeling of cast work -in-situ pile with leading borehole and enlarged base for isotropic basic and for transversely-isotropic medium were compared. Reality of decisions obtained by modeling are provided by properties of ultimate elements, by sizes of calculated field, by choice of design schemes of soil compaction, by conformity of model state soil parameters.
Keywords: soil natural and directed anisotropy; foundation; soil compaction zone; orthotropic medium; method of ultimate elements; axis-symmetrical problem